INCREASING STUDENTS’ READING COMPREHENSION ABILITY ON DESCRIPTIVE TEXT BY USING LANGUANGE EXPERIENCE APPROACH AT THE TENTH GRADE OF SMA NEGERI 1 LAHOMI - Waruwu, Opirman (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
The purpose of this study is to improve the reading comprehension skills of SMA Negeri 1 Lahomi tenth grade students by utilizing the Language Experience Approach. This study was developed using the use of classroom action research (CAR). Thirty-two students from X-MIPA 2 SMA Negeri 1 Lahomi served as research subjects. The instruments utilized to collect the data were the written test and the observation paper. Two cycles of two sessions each were used for action research in this study. Each cycle consisted of four steps: plan, action, observation, and reflection. Data were collected in both qualitative and quantitative forms. The multiple choice test yielded the quantitative data, while the observation sheet offered the qualitative data. The results of the researcher's observation sheet for the first meeting in cycle I were 72%, and for the second meeting, 84%, according to data analysis. Students' cycle I observation sheet results for the first meeting were 71%, and for the second meeting, 81%. In cycle II, the researcher's observation sheet yielded an 83% result for the first encounter and a 90% result for the second. In the first meeting, the cycle II student observation sheet result was 85%, and in the second meeting, it was 88%. Additionally, the average score for students in cycle I was 61, whereas it was 74 in cycle II. The conclusion drawn from the data is that the Language Experience Approach is a useful strategy for teaching reading. The Language Experience method (LEA) is advised for English teachers to use while instructing students in reading descriptive texts. This will assist the students become more proficient readers by using the language experience method. The researcher suggests that English teachers should use the Language Experience Approach (LEA) as one of the alternative methods to improve students' reading skills, their potential or ability with as an educator in providing information in the learning process of reading, especially when reading descriptions. Students could improve and developed their reading comprehension by using Language Experince Approach (LEA), because LEA attracted the students’ interest and motivation in teaching and learning process.